Construction of the Long Jump Test for Physical Education, Health and Recreation Students - Henjilito, Raffly; Zulkifli, Zulkifli; Zikri, Insani; Maulana, Iqmal (Universitas Majalengka, 2024)
This research aims to make improvements in the long jump test. The repaired components are only in the process of executing the stop starting from the start, support, jump and landing. Usually, the long jump test involves doing the furthest jump and measuring how far the jump is. Test instruments and norms must be used for these athletes to determine the quality of the jumps of Riau Islamic University athletic students. This research method uses research and development methods or research and development. The validation of research and development instruments uses content validation carried out by several experts (expert judgment), including one test and measurement expert and two experts in athletics. Based on the long jump expert instrument test evaluation analysis results, it was declared valid and reliable to be used as research material for athletics students.